In vitro osteogenesis process induced by hybrid nanohydroxyapatite/graphene nanoribbons composites - Reis de Vasconcellos, Luana Marotta [UNESP]; Prado, Renata Falchete do [UNESP]; Sartori, Elisa Mattias [UNESP]; Silveira Mendonca, Daniela Baccelli; Mendonca, Gustavo; Marciano, Fernanda Roberta; Lobo, Anderson Oliveira (Springer, 2019)
Carbon nanotubes combine high bend and mechanical strength, which is advantageous for many structural and biomedical purposes. Recently, some biomaterials, based on carbon nanostructures and nanohydroxyapatite (nHAp), have been investigated as bone substitutes in order to improve regeneration. The aim of this study was to access the expression of some RNA transcripts (involved in the process of osteoblast differentiation) by mesenchymal stem cells cultured over different nanocomposite surfaces. A multi-walled carbon nanotube (MWCNT) was firstly grown using chemical vapor deposition and then exfoliated using chemical and oxygen plasma treatments to obtain graphene nanoribbons (GNR). The hybrid composites nHAp/GNR were prepared using the wet method assisted by ultrasound irradiation with different amounts of GNR (1.0, 2.0 and 3.0wt %). Five groups were tested in cell cultures. Group 1: synthesized nHAp; Group 2: synthesized GNR; Group 3: nHAp and 1.0% of GNR; Group 4: nHAp and 2.0% of GNR and group 5: nHAp and 3.0% of GNR. Real time reverse transcription polymerase chain reactions were performed, and all data was submitted to Kruskal Wallis and Dunn tests, at a significance level of 5%. As a result, three nanocomposites with different proportions of GNR were successfully produced. After cell culture, the expression of osteogenic genes demonstrated no significant differences among the groups and periods. However, bone morphogenetic protein II (BMP II), integrin binding sialoprotein (IBSP), and Osterix highest expressions were observed in the group containing 3.0% of GNR. In conclusion, our hybrid composites may be useful in bone interventions requiring mesenchymal stem cell differentiation into osteoblasts for healing. [GRAPHICS] .